Pemberdayaan UMKM Sebagai Usaha Meningkatkan Kualitas Pemasaran Produk Di Padukuhan Dukuhsari Wonokerto Turi Sleman - Mansir, Firman; Tumin, Tumin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Community Service Community Service activities aim to empower the MSME community to improve product quality amid the Covid-19 outbreak that hit Indonesia. The fact is that it has an impact on economic aspects, especially MSMEs, to become stagnant. As a result, most MSME actors are hampered and even end up in bankruptcy. This is why MSME business actors change their sales plans through the digitalization program. The digitalization program in question maximizes the marketplace and establishes social media as a marketing procedure. In addition, digital MSME actors are required to be able to work with netizens when selling products and services. Thus, the plan to continue the sustainability of digital MSMEs can be one of the preferences in developing businesses amid the Covid-19 outbreak.